The secret thoughts of successful women : why capable people suffer from the impostor syndrome and how to thrive in spite of it - Young, Valerie, Ed.D. (New York : Crown Business, 2011)
An internationally known speaker, Valerie Young has devoted her career to understanding women's most deeply held beliefs about themselves and their success. In her decades of in-the-trenches research, she has uncovered the often surprising reasons why so many accomplished women experience this crushing self-doubt. In The Secret Thoughts of Successful Women,Young gives these women the solution they have been seeking. Combining insightful analysis with effective advice and anecdotes, she explains what the impostor syndrome is, why fraud fears are more common in women, and how you can recognize the way it manifests in your life.
Feel like an impostor? Join the club -- Consider the source -- It's not all in your head -- Hiding out -- What do luck, timing, connections, and personality really have to do with success? -- The competence rule book for mere mortals -- Responding to failure, mistakes, and criticism -- Success and the female drive to care and connect -- Is it'fear' of success or something else? -- Why'fake it'til you make it' is harder for women-and why you must -- Rethinking risk-taking cultivating chutzpah -- Playing big.
Includes bibliographical references and index.
Keywords: Women -- Psychology; Success